2017
DOI: 10.5530/pj.2017.6.146
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular L-Asparaginase from Streptomyces labedae VSM-6: Isolation, Production and Optimization of Culture Conditions Using RSM

Abstract: Objective: The present study was intended to isolate actinomycetes VSM-6 from deep sea sediment samples of Bay of Bengal that is potent to produce L -asparaginase. Materials and Methods: The identification of the isolate was executed by polyphasic taxonomy.Optimization was carried out using one factor at a time (O-F-A-T) for the production of the L-asparaginase. RSM was pledged to optimize the L -asparaginase production by S.labedae VSM-6. Central composite design was applied to study the influence of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The X0 value was obtained experimentally as a reference from the initial aggregated bacteria to the experiment; and through this initial value and a Matlab iteration, a theoretical biomass result was obtained to get a value similar to the experimental data. The proposed logistic model was adequate to explain the sigmoidal profile of bacterial growth as reported previously [37].…”
Section: Microbial Growthsupporting
confidence: 72%
See 3 more Smart Citations
“…The X0 value was obtained experimentally as a reference from the initial aggregated bacteria to the experiment; and through this initial value and a Matlab iteration, a theoretical biomass result was obtained to get a value similar to the experimental data. The proposed logistic model was adequate to explain the sigmoidal profile of bacterial growth as reported previously [37].…”
Section: Microbial Growthsupporting
confidence: 72%
“…Liu and Zajic in 1972 reported that lactose was the best carbon source to optimize the production of L-asparaginase from Erwina aroideae [52], however, there are few studies that reported lactose as the best carbon source for Streptomyces. In previous studies, it has been reported that L-asparagine is a suitable nitrogen source for the production of L-asparaginase by Streptomyces venezuelae, S. karnatakensis, S. collinus, S. gulbargensis and P. endphytica [37]. Several studies have shown that when using the combination of two nitrogen sources in the medium, the production of L-asparaginase increases [37,53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangamuri et al . 40 used one factor at a time and CCD to evaluate the effect of various physico-chemical factors on L-asparaginase production by Streptomyces labedae VSM-6. Maximum L-asparaginase production (8.92 U/mL) by Streptomyces labedae VSM-6 using conventional one factor at a time optimization was found after 6 th day of incubation in production medium supplemented with 1% L-asparagine, 1.5% starch, 1% yeast extract at initial pH 8 after 144 h of incubation.…”
Section: Resultsmentioning
confidence: 99%